2023
DOI: 10.1021/acsanm.3c01212
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of High-Loading Cu Single-Atom Nanozyme for Total Antioxidant Capacity Sensing

Xueliang Liu,
Fangfang Wu,
Xiangzhen Zheng
et al.

Abstract: Single-atom catalysts (SACs) with atomically dispersed active sites and maximum atomic utilization efficiency provide new opportunities to develop high-performance nanozymes. However, the preparation of SACs with a high metal content still faces serious challenges. Herein, we report a pyrolysis method for achieving a Cu single-atom catalyst (Cu-SAC) on nitrogen-doped carbon with a Cu loading of 7.98 wt %. Isolated Cu atoms with Cu–N3–C coordination were confirmed by spherical aberration-corrected transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The high-resolution spectrum of O 1s showed a new peak at 530.9 eV, which was attributed to the Cu–O bond (Figure E) . Similarly, the high-resolution spectrum of N 1s at 400.6 eV was attributed to the Cu–N bond (Figure F) . The results indicated that the Cu 2+ bonded with Trp through Cu–O and Cu–N bonds .…”
Section: Resultsmentioning
confidence: 85%
“…The high-resolution spectrum of O 1s showed a new peak at 530.9 eV, which was attributed to the Cu–O bond (Figure E) . Similarly, the high-resolution spectrum of N 1s at 400.6 eV was attributed to the Cu–N bond (Figure F) . The results indicated that the Cu 2+ bonded with Trp through Cu–O and Cu–N bonds .…”
Section: Resultsmentioning
confidence: 85%
“…Because of their simplicity and portability, colorimetric sensors offer a more appealing alternative, enabling target analysis through observable color changes. However, colorimetric approaches only provide the qualitative or semiquantitative analysis of target concentrations perceptible to the naked eye, with quantitative analyses still reliant on ultraviolet–visible (UV–vis) absorption spectrometry. Because of increasing demand for on-site quantitative analysis, the conversion of TAC information into easily measurable signals has emerged as an important research focus.…”
Section: Introductionmentioning
confidence: 99%
“…Nanozymes, that is, nanomaterials with intrinsic enzyme-like catalytic activity, attract widespread attention for their merits over natural enzymes, such as tunable activity, environmental tolerance, and easy synthesis and storage. Given these advantages, nanozymes have been implemented in several fields. Especially in the bioanalytical field, nanozymes with oxidoreductase-like activity are gradually replacing natural enzymes (like horseradish peroxidase) in the development of optical analytical methods. , Among these nanozyme-based optical sensors, colorimetric detection depending on the nanozyme-catalyzed oxidation of chromogenic substrates is widely studied due to its inherent virtues of simplicity, rapidness, and low cost. However, most colorimetric sensors are based on a single colorimetric or fluorescent signal output, susceptible to outside interference (redox substances, color distractors etc.…”
Section: Introductionmentioning
confidence: 99%